Процесс переваривания пищи у клещей-фитосейид Phytoseiulus persimilis, Amblyseius andersoni и A. reductus (Gamasoidea, Phytoseiidae) - Старовир, И.С.; Барабанова, В.В. (Вестник зоологии, 1981)
It is determined that food composition in Phythoseiulus persimilis, Amblyseius andersoni and A. reductus affected the ratio and activity of digestive enzymes, pH-optima of their action and the phytolitic index. As these mites should digest the vegetative content from guts of their victim, the mentioned indices characterize them as optional carnivores with additional vegetative nutrition.